The Patterns of Interpersonal Communication in Building an Anti-Corruption Culture Among Customs Officers’ Families in Medan City - Muhammad Tarmizi; Suwardi Lubis; Iskandar Zulkarnain (Riviera Publishing, 2024)
This research aims to analyze the patterns of interpersonal communication in building an anti-corruption culture among customs officers' families in Medan City, analyze the forms of interpersonal communication messages conducted by customs officers' families, and analyze the barriers to interpersonal communication in building an anti-corruption culture among customs officers' families in Medan City. The theory utilized in this research is Joseph A. Devito's theory of interpersonal communication. The research method employed is qualitative research. The number of informants in this study is five customs officers, with criteria including being married, residing in Medan City, and receiving recognition as an Officer of the Month or Officer of the Year. Data collection is conducted through interviews and passive participation observation. The results of this study indicate that the pattern of interpersonal communication in building an anti-corruption culture among customs officers' families in Medan City is through the equality pattern of communication. Interpersonal communication messages used in building an anti-corruption culture among customs officers' families include informative and persuasive messages. The barriers to interpersonal communication in building an anti-corruption culture among customs officers' families include semantic and psychological noise. The married couples in this study agree that interpersonal communication within a family plays a crucial role in building an anti-corruption culture.